Geochemical insights into the role of metasomatic hornblendite in generating alkali basalts - Li‐Qun Dai; Zi‐Fu Zhao; Yong‐Fei Zheng (Geochemistry, Geophysics, Geosystems)
Abstract Experimental petrology suggested the role of hornblendite in generating alkali basalt. This mechanism is confirmed by an integrated study of major‐trace elements and radiogenic isotopes for Mesozoic alkali basalts from the Qinling orogen in China. The alkali basalts have high contents of MgO (4.8–11.1 wt %, Mg# = 47–69), Na2O + K2O (2.9–5.4 wt %), TiO2 (2.0–3.1 wt %) but low content of SiO2 (41.4–49.6 wt %), which are generally silica‐undersaturated with normative minerals of nepheline and olivine. They exhibit OIB‐like trace element distribution patterns, with enrichment of LILE and LREE but no depletion of HFSE relative to the primitive mantle. They also show relatively depleted Sr‐Nd‐Hf isotope compositions, with low initial 87Sr/86Sr ratios of 0.7028–0.7058, positive εNd(t) values of 4.0–9.8 and εHf(t) values of 8.8–13.5 for whole‐rock, and positive εHf(t) values of 5.2–16.4 for zircon. Such element and isotope features indicate their origination from the juvenile subcontinental lithospheric mantle (SCLM) source with involvement of crustal components. The alkali basalts generally have high K2O/Na2O ratios, and high K2O and TiO2 contents, suggesting their derivation from partial melting of hornblendite‐rich mantle lithology. They also exhibit variable K/La and Ti/La ratios that are correlated with (La/Yb)N ratios, indicating a geochemical heterogeneity of the SCLM source. Taken together, all the above geochemical features can be accounted for by partial melting of a hornblendite‐rich SCLM source. The hornblendite would be generated by reaction of the juvenile SCLM wedge peridotite with hydrous felsic melts derived from subducted Palaeotethyan oceanic crust at the slab‐mantle interface in the subduction channel. Therefore, orogenic alkali basalts record recycling of the subducted fossil oceanic crust, and the metasomatic hornblendite is an important lithology in local SCLM domains above fossil subduction channels.